Sensory and Microbiological Analysis of Tiger Nut (Cyperus esculentus) Beverage - Sa'id, A.M; Abubakar, H.; Bello, B. (Pakistan Journal of Nutrition, 2017)
Background and Objective: Tiger nut (Cyperus esculentus) is an edible perennial grass-like plant of the Sedge family. It is widely used for human and animal consumption as a nutritious food and feed in Africa, Europe and America. Tiger nut can be eaten raw, roasted, dried, baked or made into a refreshing beverage which is very nutritive and healthy both for the young and old. There were many attempts to industrialize the locally prepared tiger nut beverage, but the inability to preserve the drink for a long time without spoilage has been a major drawback. Therefore, understanding the cause of the spoilage and promoting the process of production of the beverage from local home consumption to wider commercial consumption are the major objectives of this research study. Materials and Methods: Tiger nut tubers were processed into 4 major groups through different processing treatments, water soaked tiger nut beverage (WSTB), roasted tiger nut beverage (RTB), methanol soaked tiger nut beverage (MSTB) and boiled tiger nut beverage (BTB). Each of these mixtures was divided into two portions, one treated with Nisin (an antibiotic preservative) and the other portion left untreated. The two portions were further divided into two treatment, one stored at refrigerating temperature and the other one at room temperature, making 4 different treatments per mixture and a total of 16 samples. The samples were subjected to sensory and microbial analyses. Results: The results of the sensory analysis, colour, flavour, taste, mouth feel and overall acceptability showed that the water soaked tiger nut beverage samples were significantly different (p<0.05) than the other treatments. WSTB samples had the highest overall acceptability while BTB had the least. Microbiological analysis was carried out over a 3 week storage period. The products were microbiologically stable during the first week, but a rapid growth of microorganisms was observed after the 1st week which was high enough to cause spoilage. Conclusion: Results of the study indicated that processing treatments has effect on the stability and acceptability of tiger nut beverage products.